ACUTE TOXICITY TEST OF LOW CALCIUM OXALATE PORANG (Amorphophallus mueleri BLUME) FLOUR - Donowarti, I.; Widjanarko, S. B.; Yunianta, Y.; Pudjiastuti, P. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2021)
A field experiment Porang (Amorphophallus mueleri Blume) has the potential to be developed as a functional food ingredient because it contains high levels of glucomannan. Research on the acute toxicity test of macerated porang flour has been carried out. The results of research showed a toxic effect which was characterized by high SGOT and sodium levels. The purpose of this study was to find out the safety level of consuming porang flour with lowered calcium oxalate content. This research was an experimental study designed in one directional-pattern Completely Randomized Design using 5 treatments of porang flour administration with doses of 0; 5; 50; 500; 5000 and 15000 mg/kgbw and 6 repetitions for 60 days using Wistar-strain white rats (Rattus norvegicus) as laboratory animals. The results showed that during the treatment, the administration up to a dose of 500 mg/kgbw did not give a significant difference to all observed variables. The administration of 5000 and 15000 mg/kgbw gave a significant difference on the changes in body weight, the addition of the amount of water drunk, the levels of Calcium, Potassium and Sodium in the blood, SGOT and SGPT values, and observation on necrotic cells in the kidneys. The administration of the highest porang flour dosage, namely 15000 mg/kgbw did not cause any rat mortality and did not cause any real cell damage to the liver, but caused hyperactive behavior in female rats.